Viticulture in Santorini Island: current trends and challenges - Efstratios G. XYRAFIS (Notulae Botanicae Horti Agrobotanici Cluj-Napoca)
The Santorini vineyard is a unique and extreme vineyard on a global scale with economic, historical and wine value. It also constitutes the second largest activity after tourism although linked to it. The special soil-climatic conditions and the specificity of viticulture on the island make it uniquely distinct and therefore a field of interdisciplinary study and research at a local and global level. However, the aging of the vineyard, the reduction of its cultivation area, its non-optimal management and finally the looming effects of climate change form a set of factors that should be weighed and assessed by those involved in the sector. At the same time, the rapid changes taking place at the global level (e.g. technological innovations) create opportunities, but at the same time the context in which the brand name "Santorini" is undoubtedly part of becomes more competitive, while also entailing risks from unforeseen developments. Only with collective action and a strategic approach will it be possible to ensure a sustainable future for the vineyard of Santorini. It is up, the stakeholders of the island to take the adequate initiatives.